Electronic structure and half-metallicity of new quaternary Heusler alloys NiFeTiZ (Z=Si, P, Ge, and As). (December 2015) - Karimian, N.; Ahmadian, F.
Abstract: The electronic structure and magnetic properties of NiFeTiZ (Z=Si, P, Ge, and As) quaternary Heusler compounds were investigated using the full-potential linearized augmented plane wave (FPLAPW) method in framework of the density functional theory (DFT). The results showed that NiFeTiZ (Z=Si, P, Ge, and As) compounds were stable in YI structure and the NiFeTiP and NiFeTiSi compounds were true half-metallic (HM) ferromagnets. The NiFeTiGe had a nearly HM characteristic, while NiFeTiAs was a conventional ferromagnet. The majority and half-metallic band gaps were respectively 0.44 and 0.3 eV for NiFeTiP and 0.18 and 0.08 eV for NiFeTiSi. The origin and mechanism of the formation of majority band gap in NiFeTiP were also verified. The total magnetic moments of NiFeTiP and NiFeTiSi compounds were respectively obtained 1 μ B and 2 μ B per formula unit, which were in agreement with Slater-Pauling rule ( M tot = 28 −Z tot ). Half-metalliciy exists in relatively wide ranges of 5.43–5.80 Å and 5.60–5.87 Å for NiFeTiP and NiFeTiSi compounds, respectively, which makes them promising candidates in spintronics. Highlights: The NiFeTiZ (Z=Si, and P) quaternary Heusler alloys have HM nature. Half-metallicity is mainly relative to the hybridizations of the d states of transition metals. The E HM values are obtained 0.3 eV and 0.08 eV for Z=P, and Si, respectively. The M tot of NiFeTiZ (Z=Si, and P) alloys are in agreement with rule M tot = 28 −Z tot . NiFeTiP and NiFeTiSi compounds are half-metals between 5.43 and 5.80 Å and 5.60and 6.87 Å, respectively.